A Case of Cortical Deafness due to Bilateral Heschl Gyrus Infarct - Santhosh Narayanan; K. Abdul Majeed; Gomathy Subramaniam; Arathi Narayanan; K. M. Navaf (Case Reports in Medicine)
We report the case of a 58-year-old male who presented with an episode of seizure and abrupt onset hearing loss. Neuroimaging revealed acute infarcts in bilateral Heschl gyri. Objective tests of peripheral auditory function were essentially normal and a diagnosis of cortical deafness was made.